Chinese triads and the notion of territory - Lo, Tit Wing (Criminology & criminal justice, 2025)
Territory, where a network of influence and business interests can be developed, is an important feature of criminal organizations. While some research on organized crime by Chinese triads has been published in recent years, the concept of triad territory is still under-researched. This article discusses what a triad territory is and how it is formed, managed and defended. Through qualitative research, it is found that triad business is territorial in nature. Different triad societies have their own turfs and monopolize certain geographical territories or economic sectors. Territory is important for the survival of triad societies, not only because most of their business operates within the territory but also because they rely on the territory to maintain social networks, exchange criminal market information, gather intelligence and source business opportunities. This article concludes that a triad territory is structurally, culturally and cognitively embedded, and is a defensible social and economic space of a triad society.